PENINGKATAN HASIL BELAJAR SISWA DENGAN METODE LATIHAN PADA PEMBELAJARAN MATEMATIKA PENGURANGAN PECAHAN KELAS V SDN 101768 TEMBUNG KAB. DELI SERDANG - Zuraidah Zuraidah (JURNAL TEMATIK, 2015)
This study aims to determine whether the training method can improve learning outcomes math class V SDN 101 768 Tembung. The problem in this study is whether the training method can improve learning outcomes math class V SDN 101 768 Tembung Percut District of Sei Tuan, Deli Serdang regency. The subject of research to all fifth grade students at SDN 101 768 Tembung totaling 34 people, training method. Research was conducted on a mathematic subject